Gaps in socio-economic, generational and gender in the Peruvian education: An approach with mass data of a northern city - Arhuis-Inca, Wendy (2021)
Our aim was to determine the educational gap according to gender, socioeconomic status, and generational group among city adults. The study design was observational and cross-sectional, using data from the 2016-2017 Population Study in Chimbote, Peru. We looked at educational attainment, sex, socioeconomic status and age (for defining generational groups) of 20,005 people aged 22 years and over. Data were summarized in cross-tables and analyzed with a Chi-square test of homogeneity. The results showed that adults presented an educational gap, with a clear disadvantage in the lower socioeconomic level, particularly in the secondary and higher education level groups. Within the socioeconomic levels there are educational inequalities, evidenced in secondary and higher achievement for the poorest women and at the higher level for the younger generations of both socioeconomic levels.